The Cost-Effectiveness of Multigene Panel Testing for Hereditary Breast and Ovarian Cancer in Norway. Issue 1 (February 2019) - Asphaug, Lars; Melberg, Hans Olav
Background. Expansion of routine genetic testing for hereditary breast and ovarian cancer from conventional BRCA testing to a multigene test could improve diagnostic yield and increase the opportunity for cancer prevention in both identified carriers and their relatives. We use an economic decision model to assess whether the current knowledge on non- BRCA mutation prevalence, cancer risk, and patient preferences justifies switching to a multigene panel for testing of early-onset breast cancer patients.Methods. We evaluated routine testing by BRCA testing, a 7-gene panel, and a 14-gene panel using individual-level simulations of annual health state transitions over a lifetime perspective. Breast and ovarian cancer incidence is reduced and posttreatment survival is improved when high-risk mutations are detected and risk-reducing treatment offered. Most model inputs were synthesized from published literature. Intermediate health outcomes included breast and ovarian cancer incidence rates, along with organ-specific cancer mortality. Cost-effectiveness outcomes were health sector costs and quality-adjusted life years.Results. Intermediate health outcomes improved by testing with multigene panels. At a cost-effectiveness threshold of $77, 000, a 7-gene panel test with five non- BRCA genes was the optimal strategy with an incremental cost-effectiveness ratio of $53, 310 per quality-adjusted life year compared to BRCA -only testing.Limitations. Unable to stratify carriers to specific mutations within genes, we can only make predictions on the gene level, with combined risk estimates for known variants. As mutation prevalence is the absolute upper bound of returns to more expansive testing, the rarity of modelled mutations makes analysis outcomes sensitive to model implementation.Conclusions. A 7-gene panel to diagnose hereditary breast and ovarian cancer in early-onset breast cancer patients can be a cost-effective alternative to current BRCA -only testing in Norway.